Diagnosis and treatment of heart failure in hereditary transthyretin amyloidosis - Puig-Carrion, Gisela D. (Clin Auton Res, 2019)
Amyloidosis describes a family of related disease states associated with the extracellular tissue deposition of fibrils composed of low-molecular-weight subunits of a variety of proteins circulating as constituents of plasma. Depending on the disease subtype, fibrillar deposits in a several organs including the heart, kidney, liver, and peripheral nerves cause organ dysfunction and associated morbidity and mortality. The most common amyloid fibril deposits associated with cardiac manifestations are of monoclonal light-chain or transthyretin (ATTR) types. This review will focus on the ATTR types of cardiac amyloidosis. ATTR amyloidosis may be associated with abnormal metabolism of wild-type transthyretin (previously called senile systemic amyloidosis) or with hereditary variants in the transthyretin gene. Cardiac amyloidosis is often under-recognized in its early stages, and when a diagnosis of cardiac amyloidosis is made, patients are often at the advanced stages of the disease. Treatments now available appear to exert their benefit predominantly in individuals with the early stages of disease. Increased awareness and early diagnosis of cardiac amyloidosis and continued discovery of effective therapies will increase opportunities to improve clinical outcomes in this patient population.